Transgenic mice applications in the study of endometriosis pathogenesis - Zhao, Yali; Wang, Yao; Gu, Pinlang; Tuo, Lingjin; Wang, Leilei; Jiang, Shi-Wen (Frontiers in Cell and Developmental Biology, 2024)
Endometriosis (EM), characterized by chronic ectopic growth of endometrial tissues and recurrent pelvic pain, is a common disease with severe negative impacts on the life quality of patients. Conventional uterine tissue transplantation-based models are have been broadly used to investigate the pathogenic mechanism(s) of EM. Transgenic mice with whole body or uterine/pelvic tissue-specific labelling by the expression of GFP, -gal or other light-emitting or chromogenic markers enable investigators to analyze the contribution to endometriotic lesions by the donor or recipient side after uterine tissue transplantation. Moreover, when coupled to uterine tissue transplantation, transgenic mice with a specific EM-related gene knocked out or overexpressed make it possible to determine the gene's in vivo role(s) for EM pathogenesis. Furthermore, observations on the rise of de novo endometriotic lesions as well as structural/functional changes in the eutopic endometrium or pelvic tissues after gene manipulation will directly relate the cognate gene to the onset of EM. A major advantage of transgenic EM models is their efficiency for analyzing gene interactions with hormonal, dietetic and/or environmental factors. This review summarizes the features/sources/backgrounds of transgenic mice and their applications to EM studies concerning hormonal regulation, angiogenesis and inflammation. Findings from these studies, the advantages/disadvantages of transgenic EM models, and future expectations are also discussed.